STUDI KUALITAS AIR DANAU SINGKARAK UNTUK BUDIDAYA IKAN KERAMBA (IKAN MAS, IKAN NILA, IKAN LELE IKAN GURAMI, IKAN BAWAL, IKAN BETUTU DAN IKAN PATIN) DI KABUPATEN SOLOK SUMATERA BARAT - Prawita, Inda; Dasrizal, Dasrizal; Zuriyani, Elvi (Pendidikan Geografi, 2013)
This study aims to assess the feasibility of water quality of Danau Singkarak for cage fish farming. The method used is descriptive analysis in order to make a picture of systematic factual and accurate based on the feasibility of water quality parameters in measuring the physical parameters of the water temperature and the residue suspended and water chemistry parameters pH, dissolved oxygen (DO), phosphate, ammonia (NH3 ). Danau Singkarak by setting three sample points, namely: Kenagarian Tikalak (sample A) suitable for cultivated species of tilapia and catfish. Kenagarian Singkarak (sample C) suitable for cultivated species of catfish, carp and fish betutu. In Kenagarian Kacang (sample B) do not fit in aquaculture of all species of fish examined. Because there is have high temperature in Kenagarian Kacang and value of acidity (pH) also resulted in the growth of this high-stunted fish.